JavaScript Creativity Exploring the Modern Capabilities of JavaScript and HTML5 - Hudson, Shane; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2014)
JavaScript Creativity teaches you how to use every feature of this versatile and powerful language in exciting and creative ways. JavaScript can be used for so much more than simple interactivity. Master your use of canvas, animation, audio and video, 3D visualizations, motion detection and real-time collaboration. In every chapter of this book you will learn how to use and evolve JavaScript's creative capabilities in your own projects, as well as having project examples to follow throughout. Specifically, you will learn how to: Expertly use canvas and animation Push audio and video to their full capabilities Code and manipulate advanced 3D visualizations Create your own music directly from the browser Implement real-time collaboration with Node.js Explore real-time audio and video with WebRTC Play with motion detection and gesture control Combine all features into one social music creation experiment, similar to Google's 'Jam with Chrome' JavaScript Creativity is for the developer who has a working knowledge of JavaScript and wants to take their code to the next level. Every feature explored can be manipulated and implemented in your everyday projects to really impress your clients or just increase your code skill. This book is an exciting, action-packed introduction to all the advanced and truly creative aspects of this language - start creative coding today!
Keywords: Computer programming; Software engineering; Web Development; Software Engineering/Programming and Operating Systems